Seroepidemiological Pattern Of Brucellsis Among Buffaloes In Northgujarat - Panchasara, H.H.; Patel, J.S.; Patel , P. R. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Sero surveillance of brucellosis was carried out in buffaloes belonging to different organized farms and villages of North Gujarat during 2003-2005. Total 1088 heads of buffaloes were screened for brucella antibodies by Rose Bengal Plate Agglutination Test (RBPT), Standard Tube Agglutination Test (STAT) and indirect Enzyme Linked Immuno Sorbant Assay (i ELISA). Overall sero prevalence was 10.66, 10.29 and 9.38 by RBPT, STAT and i ELISA among buffaloes. Higher prevalence was observed in field cases. Irrespective of breed, older animals (> 12 years of age) had significantly higher infection rate (25.00 %) than younger animals (1.38 %). Sero prevalence rate showed upward trend with successive lactations. Higher sero prevalence rate was observed among female animals. Pregnant heifers showed significantly higher sero prevalence as compared to unconceived heifers. Overall sero prevalence with the history of abortion, retained placenta, repeat breeder, abortion and ROP, abortion and RB, ROP and RP or all the three were 20.51,22.22, 8.82,11.76, 20.00,17.65 and 38.09 per cent, respectively. Seropositivity in the buffaloes of organized farms was 3.45 and 14.29 per cent in apparently healthy buffaloes and buffaloes with reproductive problems.